Pengaruh Penghindaran Pajak, Profitabilitas Dan Leverage Terhadap Nilai Perusahaan: Transparansi Informasi Sebagai Variabel Pemoderasi - Pramessita Berliany; Rina Trisnawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the influence of tax avoidance, profitability, and leverage on firm value, with transparency of information as a moderating variable, focusing on food and beverage companies listed on the Indonesia Stock Exchange (IDX) during 2019-2022. The research uses an associative design with a quantitative approach to analyze the relationships between the independent variables (tax avoidance, profitability, and leverage) and firm value. The sample consists of companies from the food and beverage sector selected using purposive sampling, based on specific criteria. Data was obtained from secondary sources in the form of annual reports, and analyzed using multiple linear regression, classical assumption tests, descriptive analysis, and hypothesis testing. The results indicate that tax avoidance and leverage do not have a significant impact on firm value, either directly or moderated by transparency of information, while profitability has a significant positive effect on firm value. Additionally, transparency of information does not moderate the relationship between profitability and leverage and firm value.